Implikasi Globalisasi dan Penegakan Hukum Progresif di Indonesia - Dharma Setiawan Pagaralam (PRANATA HUKUM, 2011)
The Pancasila role in law national development at globalization era, globalization affects the economic, political and legal culture, making the relationship the countries is becoming one global village. The aspect of substance by the increasing adopted liberalism or neo-liberalism; and the cultural aspects affect the attitudes and behaviors that tend to be individualistic society. The Pancasila as an ideology and the basic state of Indonesia in the development of national law is a necessary âstaatsfundamentalnorm or rechtsidee " to elaborated in the principles of law and implementing of law The Pancasila as well as a filter for conformance to international legal instruments that will be enforced; as well as guidance for state and government agencies in formulating, implementing, and enforcing, and guidelines for Indonesia people.